2020
DOI: 10.1038/s41598-020-74665-x
|View full text |Cite
|
Sign up to set email alerts
|

Stress erythropoiesis in atherogenic mice

Abstract: Bone marrow erythropoiesis is mainly homeostatic and a demand of oxygen in tissues activates stress erythropoiesis in the spleen. Here, we show an increase in the number of circulating erythrocytes in apolipoprotein E−/− mice fed a Western high-fat diet, with similar number of circulating leukocytes and CD41+ events (platelets). Atherogenic conditions increase spleen erythropoiesis with no variations of this cell lineage in the bone marrow. Spleens from atherogenic mice show augmented number of late-stage eryt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…S4C). Among the different late erythroblasts, gated as described in ( 32 ) and fig. S5 (A and B), infected hypothyroid mice showed a reduced number of Ery B with respect to the euthyroid mice, and Ery C supported in both groups the major increase at day 6 after infection (fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S4C). Among the different late erythroblasts, gated as described in ( 32 ) and fig. S5 (A and B), infected hypothyroid mice showed a reduced number of Ery B with respect to the euthyroid mice, and Ery C supported in both groups the major increase at day 6 after infection (fig.…”
Section: Resultsmentioning
confidence: 99%
“…Unstained cells were used as a negative control to establish the flow cytometer voltage settings, and single-color positive controls were used to adjust compensation. To identify the different splenic cells, without treatment with lysis solution, cells were subjected to flow cytometry analysis as described ( 32 , 64 ). The absolute number of cells was calculated by adding Perfect-Count Microspheres (CYTPCM-100, Cytognos) to the flow cytometry samples.…”
Section: Methodsmentioning
confidence: 99%
“…Stress erythropoiesis resembles fetal erythropoiesis in many ways 39 . In a murine model of stress erythropoiesis, monocytes were recruited to the spleen and formed an erythropoiesis niche, called erythroblastic islands, with erythroid progenitors 40 , 41 . Splenic erythroid progenitors share surface markers with burst-forming unit-erythroid progenitors (BFU-Es) from murine fetal liver 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Hemeoxygenase-1 (HO-1) has been shown to have anti-AS effects [50], and its production is increased in AS. Additionally, Sánchez et al [51] observed increased erythropoiesis in mice with AS.…”
Section: Erythrocyte Lifespan and Asmentioning
confidence: 98%